A Case of HIV at Woodworks Ltd (A) : Jai Shah's Dilemma - Sharda, Kirti (London : Indian Institute of Management, Ahmedabad, 2020)
Raman Basu, an employee at Woodworks Ltd. has tested positive for HIV; Jai Shah, the CEO of the firm (and the protagonist in this case) wants to take a decision whether the employee should be asked to leave the organization or be retained. The case situation offers an opportunity to engage in an in-depth discussion of the overt and unconscious discrimination faced by individuals suffering from HIV/AIDS in workplaces. Parallel events in the case also create scope to explore negative effects of social attitudes such as stereotyping and prejudice, which could also lead to discrimination, especially towards immigrant employees. The case discussion closes with an examination of the leadership actions needed in potentially discriminatory situations.
Description based on XML content.
Keywords: elektronické knihy; electronic books; HIV-positive persons -- Employment; AIDS (Disease) -- Patients -- Employment; Personnel management